2020
DOI: 10.21203/rs.3.rs-89412/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Multi-Centre Survey on Hospital Malnutrition: Result of PNSI Study

Abstract: Background: Disease-related malnutrition is associated with adverse outcomes such as increased rates of morbidity and mortality, prolonged hospital stay, and extra costs of health care. This study was conducted to assess nutritional status among patients and to determine the risk factors for malnutrition in Iran university hospitals. Methods: Persian Nutritional Survey In Hospitals (PNSI) was a cross-sectional study that conducted in 20 university hospitals across Iran. All the patients with age range of 18 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
2
0
3
Order By: Relevance
“…Colorectal cancer had induced weight loss in 35.6% of patients. The prevalences of nutritional risk and malnourishment in our study were consistent with those reported previously 2,[18][19][20] .…”
Section: Discussionsupporting
confidence: 92%
“…Colorectal cancer had induced weight loss in 35.6% of patients. The prevalences of nutritional risk and malnourishment in our study were consistent with those reported previously 2,[18][19][20] .…”
Section: Discussionsupporting
confidence: 92%
“…El 50 % (n = 8) de los pacientes refirió haber perdido peso en los últimos tres meses; la mediana de pérdida de peso fue de 6 [4][5][6][7][8][9][10] kg. Solo un paciente refirió haber disminuido su ingesta de alimentos debido a la inapetencia.…”
Section: Riesgo De Desnutriciónunclassified
“…Los factores de riesgo para la desnutrición incluyen edad avanzada (5) , presencia de enfermedades crónicas, pluripatología, polifarmacia, fragilidad e ingesta inadecuada de alimentos, todas características comunes entre la población de pacientes de medicina interna (6,7) . Adicionalmente, varios estudios han informado asociaciones significativas entre el riesgo nutricional y un aumento de mortalidad hospitalaria (8)(9)(10) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A multicenter Canadian study published in 2016 reported that 45% of medical and surgical patients who stayed in hospital for more than two days had some degrees of malnutrition on admission based on subjective global assessment (SGA) (1) . Persian Nutritional Survey In Hospitals (PNSI), a multi-center survey in Iranian hospitals, found that roughly a quarter of patients were malnourished (SGA-B & C) (2) . Also, findings of NutritionDay in the US hospitals indicated that 32.7% of patients were malnourished or at nutritional risk (malnutrition screening tool (MST) score ≥2) (3) .…”
Section: Introductionmentioning
confidence: 99%